Effects of flowering period on floral traits, pollinator behavior and seed production of David’s mountain laurel (Sophora davidii) - Chengtao Pan; Zhimin Chen; Mao Zhang; Xiangsheng Chen; Guy Smagghe; Mingyu Fan; Zhimin Chang; Lili Zhao; Jiankun Long (Plant Signaling & Behavior)
Sophora davidii is a cross-pollinated plant with important ecological protection and medicinal value in China, but its seed yield is low due to backward and nonstandard production technology. Therefore, we divide the flowering period of Sophora davidii into initial, full and final flowering period, measuring the floral morphology, pollen viability, stigma receptivity, nectar volume and nectar concentration, foraging behavior of pollinators, fertilization physiology, seed yield and quality through field observation and indoor testing to explore whether the flowering period affects the floral traits, pollinator behavior and seed production of plants. Our results revealed that the nectar volume, nectar concentration, pollen viability and stigma receptivity at full flowering period were the highest. The single visit time and visit time per flower of Chinese honey bees were the longest in the full flowering period, while the number of transfer, visit frequency and number of touching stigma were the least. The visiting number of the bees was the most and the most active in the full flowering period. The bees pollination not only improved the pollen amount, germination rate, pollen tube length and the ovule number of S. davidii, but also their effect was the most obvious in full flowering period. The principal component analysis showed that pollination by Chinese honey bees during the whole flowering period of S. davidii was the best way to produce seeds. We can conclude that flowering period affects flower traits, foraging behavior of pollinators, seed yield and quality of S. davidii.